Integrative genomics reveals paths to sex dimorphism in Salix purpurea L. (1st August 2021) - Hyden, Brennan; Carlson, Craig H; Gouker, Fred E; Schmutz, Jeremy; Barry, Kerrie; Lipzen, Anna; Sharma, Aditi; Sandor, Laura; Tuskan, Gerald A; Feng, Guanqiao; Olson, Matthew S; DiFazio, Stephen P; et al.
Abstract: Sex dimorphism and gene expression were studied in developing catkins in 159 F2 individuals from the bioenergy crop Salix purpurea, and potential mechanisms and pathways for regulating sex development were explored. Differential expression, eQTL, bisulfite sequencing, and network analysis were used to characterize sex dimorphism, detect candidate master regulator genes, and identify pathways through which the sex determination region (SDR) may mediate sex dimorphism. Eleven genes are presented as candidates for master regulators of sex, supported by gene expression and network analyses. These include genes putatively involved in hormone signaling, epigenetic modification, and regulation of transcription. eQTL analysis revealed a suite of transcription factors and genes involved in secondary metabolism and floral development that were predicted to be under direct control of the sex determination region. Furthermore, data from bisulfite sequencing and small RNA sequencing revealed strong differences in expression between males and females that would implicate both of these processes in sex dimorphism pathways. These data indicate that the mechanism of sex determination in Salix purpurea is likely different from that observed in the related genus Populus . This further demonstrates the dynamic nature of SDRs in plants, which involves a multitude of mechanisms of sex determination and a high rate of turnover.